On Elastic Solids with Micro‐Structure. Issue 1 (December 2014) - Picard, Rainer
Abstract Abstract. Based on the general framework of evolutionary equations in the sense of [6, 8] and referring to well‐posedness results in the context of evolutionary problems from mathematical physics we consider two problems from elasticity theory as particular applications. Our structural perspective is illustrated by showing that the theory of elastic solids with micro‐structure can be transparently embedded into the abstract solution theory. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)